The association between visceral adiposity index and decreased renal function: A population-based study - Qin, Zheng; Chen, Xinyang; Sun, Jiantong; Jiang, Luojia (Frontiers in Nutrition, 2023)
Aims We aimed to investigate the association of visceral adiposity index (VAI) with decreased renal function in US adults. Design and methods Cross-sectional data were analyzed for 35,018 adults in the National Health and Nutrition Examination Survey (NHANES) 2005–2018. VAI was determined using waist circumference, body mass index (BMI), triglycerides (TGs) and high-density lipoprotein-cholesterol. Albuminuria was defined as urinary albumin-to-creatinine ratio (ACR) >30 mg/g. A low estimated-glomerular filtration rate (eGFR) was defined as an eGFR lower than 60 ml/min/1.73 m2. Chronic kidney disease (CKD) was defined as either albuminuria or low-eGFR. A multivariable logistic regression analysis was utilized to explore the relationship of VAI with albuminuria, low-eGFR and CKD. Subgroup analysis and interaction tests were also conducted. Results A total of 35,018 participants were enrolled with albuminuria, low-eGFR, and CKD prevalence rates of 5.18, 6.42, and 10.62%, respectively, which increased with the higher VAI tertiles. After full adjustment, a positive association of VAI with albuminuria (OR = 1.03, 95% CI: 1.00, 1.06) and CKD (OR = 1.04, 95% CI: 1.02, 1.06) was observed. Participants in the highest VAI tertile had a significantly 30% increased risk for albuminuria (OR = 1.30, 95% CI: 1.07, 1.58) and a 27% increased risk for CKD (OR = 1.27, 95% CI: 1.08, 1.49) compared with those in the lowest VAI tertile. No statistically significant association between VAI and low-eGFR was detected. Subgroup analysis and the interaction term indicated that there was no significant difference among different stratifications. Conclusion Visceral adiposity accumulation evaluating by VAI was associated with increased likelihood of the decline in renal function.